DEVELOPMENT OF AN EFFECTIVE TECHNOLOGY FOR PRODUCING SOY MILK FROM LOCAL SOY RAW MATERIALS, STUDYING ITS COMPOSITION AND PHYSICAL AND CHEMICAL PROPERTIES - Rakhimova, Gulmira (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this study, the issues related to the development of an efficient technology for producing soy milk from local soybean varieties were examined. The research investigated the effects of the soybean-to-water ratio (hydromodule) and soaking temperature on the quality of the obtained soy milk. It was established that at a hydromodule of 5:1, the chemical composition of soy milk is the most comparable to that of cow’s milk, and the extraction of proteins from soybeans into the aqueous phase occurs most intensively. The optimal soaking temperature for soybeans was determined to be 50 °C, at which the highest yield and best quality of soy milk are achieved.